2018
DOI: 10.3389/fpubh.2018.00117
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Long-Term Adverse Health Effects in Oil Spill Cleanup Workers of the Deepwater Horizon Offshore Drilling Rig Disaster

Abstract: BackgroundThe purpose of this study was to assess the long-term adverse health effects of the 2010 Deepwater Horizon Gulf oil spill exposure in workers who participated in its cleanup work.MethodsMedical charts of both the oil spill exposed and unexposed subjects were reviewed. The changes in the white blood cells, platelets, hemoglobin, hematocrit, blood urea nitrogen, creatinine, alkaline phosphatase (ALP), aspartate amino transferase (AST), alanine amino transferase (ALT) levels, as well as their pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 38 publications
(51 reference statements)
1
17
0
Order By: Relevance
“…Oil spills involve health risks for humans participating in cleanup or inhabiting or otherwise using the surrounding affected area (Laffon et al 2016). Respiratory problems have been documented in cleanup workers following the Deepwater Horizon spill (Alexander et al 2018; D'Andrea and Reddy 2018). Other human health impacts were recently reviewed following several major crude oil or heavy fuel oil (bunker C) spill accidents (Aguilera et al 2010; Goldstein et al 2011; Levy and Nassetta 2011; Laffon et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Oil spills involve health risks for humans participating in cleanup or inhabiting or otherwise using the surrounding affected area (Laffon et al 2016). Respiratory problems have been documented in cleanup workers following the Deepwater Horizon spill (Alexander et al 2018; D'Andrea and Reddy 2018). Other human health impacts were recently reviewed following several major crude oil or heavy fuel oil (bunker C) spill accidents (Aguilera et al 2010; Goldstein et al 2011; Levy and Nassetta 2011; Laffon et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the aftermath of the DHOS, various forms of spill exposure have been linked to increased physical health symptoms, including wheezing and shortness of breath, headaches, skin rashes, and burning of the eyes, nose, throat, and lungs (D'Andrea and Reddy 2013;Fan et al 2015;Peres et al 2016). Among cleanup workers, illness symptoms-including hematological, hepatic, pulmonary, and cardiac functions-have been worsening over time (D'Andrea and Reddy 2018).…”
mentioning
confidence: 99%
“…Our preliminary studies on the potential health effects of the oil spill exposure from the Horizon drilling rig blasting disaster revealed that human exposure to this oil spill has a potential to disrupt hematological, hepatic and other organ functions [15]. The longterm follow up analysis demonstrated that individuals involved in the oil spill cleanup operations experienced persistent alterations or worsening of their hematological, hepatic, pulmonary and cardiac functions [16]. To further substantiate the findings of these studies, we conducted a larger study to assess the adverse health effects of the Gulf oil spill exposure in workers participating in the clean-up activities.…”
Section: Introductionmentioning
confidence: 94%